Impact of Paradoxical Leader Behavior (PLB) on Employees’ In-Role and Extra-Role Performance in the Hospitality Industry: Moderating Role of Psychological Capital - Mehreen Fatima; Naveed Akhtar; Hafsah Zahur (Journal of Management and Research)
This study aims to examine the direct association between paradoxical leader behavior and the followers’ in-role and extra-role performance in the hospitality industry. Furthermore, this study also analyzes the moderating role of psychological capital. Data was collected through a questionnaire from supervisors and their immediate frontline employees working in the hospitality industry (specifically operating in the twin cities of Rawalpindi and Islamabad, Pakistan). The results of multilevel path analysis demonstrated that paradoxical leader behavior (PLB) is positively associated with in-role and extra-role performance of frontline employees. Moreover, the followers’ psychological capital moderates the relationship between PLB and the followers’ in-role and extra-role performance, such that the relationship was determined to be stronger when the followers’ psychological capital was higher. The findings of this study extend our understanding of the construct of PLB and how it is related with the followers’ performance outcomes.